Fabrication and assessment of a bio-inspired synthetic tracheal tissue model for tracheal tube cuff leakage testing - Tamaralayefa Agbiki; Richard Arm; David W. Hewson; Sandor Erdody; Andrew M. Norris; Ricardo Correia; Sergiy Korposh; Barrie R. Hayes-Gill; Arash Shahidi; Stephen P. Morgan (BJA Open, 2024)
Introduction: Leakage of orogastric secretions past the cuff of a tracheal tube is a contributory factor in ventilator-associated pneumonia. Current bench test methods specified in the International Standard for Anaesthetic and Respiratory Equipment (EN ISO 5361:2023) to test cuff leakage involve using a glass or plastic rigid cylinder model of the trachea. There is a need for more realistic models to inform cuff leakage. Methods: We used human computerised tomography data and additive manufacturing (3D printing), combined with casting techniques to fabricate a bio-inspired synthetic tracheal model with analogous tissue characteristics. We conducted cuff leakage tests according to EN ISO 5361:2023 and compared results for high-volume low-pressure polyvinyl chloride and polyurethane cuffs between the rigid cylinder trachea with our bio-inspired model. Results: The tracheal model demonstrated close agreement with published tracheal tissue hardness for cartilaginous and membranous soft tissues. For high-volume low-pressure polyvinyl chloride cuffs the leakage rate was >50% lower in the bio-inspired tracheal model compared with the rigid cylinder model (151 [8] vs 261 [11] ml h−1). For high-volume low-pressure polyurethane cuffs, much lower leakage rates were observed than polyvinyl chloride cuffs in both models with leakage rates higher for the bio-inspired trachea model (0.1 [0.2] vs 0 [0] ml h−1). Conclusion: A reproducible tracheal model that incorporates the mechanical properties of the human trachea can be manufactured from segmented CT images and additive manufactured moulds, providing a useful tool to inform future cuff development, leakage testing for industrial applications, and clinical decision-making. There are differences between cuff leakage rates between the bio-inspired model and the rigid cylinder recommended in EN ISO 5361:2023. The bio-inspired model could lead to more accurate and realistic cuff leakage rate testing which would support manufacturers in refining their designs. Clinicians would then be able to choose better tracheal tubes based on the outcomes of this testing.